Exploring Pietism as an Intermediary for Lutheran-Pentecostal Dialogue - Brunner, Daniel L. (Dialog, 2016)
The authors, a Lutheran and a Pentecostal, explore similarities and differences between their respective traditions using German Lutheran Pietism as a bridge. Parallels include conversionism, devotion to the Bible, practical holiness, missional activism, and opposition to the shortcomings of the religious status quo. Key divergences between the movements include the role of the sacraments, the place of manifestational gifts, and eschatology. The authors highlight how Pietism can be a useful channel and translator for dialogue.